HLA-B*1502 is associated with aromatic anticonvulsant drug-induced cutaneous adverse drug reactions among the Hakka population in China. Issue 3 (March 2020) - Zheng, Zhiyuan; Zhong, Hua; Zhang, Qunji; Huang, Qingyan; Wu, Heming
Background: The purpose of this study was to analyze the correlation between aromatic antiepileptic drug-induced cutaneous adverse drug reactions and HLA-B*1502 genotype in patients from the Hakka population in Meizhou. Methods: A total of 214 epileptic patients taking aromatic (n = 94) or non-aromatic anticonvulsants (n = 120) were included in the study from September 2016 to May 2018. Clinical data for the patients were analyzed retrospectively and HLA-B*1502 genotype testing was carried out. Results: Thirty patients were HLA-B*1502(+) (14.02%). The proportion of HLA-B*1502(−) genotype and incidence of adverse drug reactions (ADRs) differed significantly between the two drug groups. In the aromatic anticonvulsant group, maculopapular eruption (MPE), Stevens–Johnson syndrome (SJS), toxic epidermal necrolysis (TEN), and hypersensitivity syndrome (HSS) occurred in 10 patients, including eight HLA-B*1502(+) and two HLA-B*1502(−) patients. MPE, HSS, SJS, and TEN occurred in 26 patients in the non-aromatic anticonvulsant group, including one HLA-B*1502(+) and 25 HLA-B*1502(−) patients. There was a significant correlation between the proportions of HLA-B*1502(+) genotype and induced cutaneous adverse drug reactions in the two groups. Conclusions: HLA-B*1502 is associated with aromatic anticonvulsant drug-induced cutaneous adverse drug reactions among the Hakka population in Meizhou, China.